High-dose Weekly Liposomal Amphotericin B Antifungal Prophylaxis in Patients Undergoing Liver Transplantation. Issue 4 (April 2015) - Giannella, Maddalena; Ercolani, Giorgio; Cristini, Francesco; Morelli, Mariacristina; Bartoletti, Michele; Bertuzzo, Valentina; Tedeschi, Sara; Faenza, Stefano; Puggioli, Cristina; Lewis, Russell E.; Pinna, Antonio Daniele; Viale, Pierluigi
<x xml:space="preserve">Abstract</x> Background To assess the safety and tolerability of high-dose weekly (10 mg/kg) liposomal amphotericin B (LamB) for antifungal prophylaxis in liver transplantation (LT) recipients with predefined risk factors for invasive fungal infection (IFI), a prospective phase II noncomparative trial was performed at our center over a 4-year period. Methods In the selected LT recipients, LamB was administered weekly until hospital discharge after LT for minimum 2 weeks. Criteria for early discontinuing prophylaxis were: (i) any adverse event (AE); (ii) suspicion of IFI. Safety and tolerability were assessed according to the incidence of grades 3 to 4 AEs based on Common Toxicity Criteria (CTC) classification. Post-LT follow-up was of 180 days. Results Overall, 76 patients were included. Liposomal amphotericin B was started within a median of 1 (interquartile range, 1–4) day after LT. Overall, 66 of 76 (86.8%) patients completed the prophylaxis, 10 discontinued the study protocol: 6 for infusion-related AE, 4 for suspected IFI. Adverse events consisted of five cases of lumbar pain and one case of thoracic pain which occurred after a median of 1.5 (interquartile range, 1–2) LamB infusions. None of the patients reported CTC grades 3 to 4 hypokalemia, three reported CTC grade 3 acute renal injury, none of which were deemed directly attributable to LamB. No drug-drug interactions with immunosuppressive drugs were reported, and no episode of rejection occurred during the prophylaxis. In only two of the four patients with suspected IFI was the diagnosis of invasive candidiasis confirmed. Conclusion Our results suggest high-dose weekly LamB may be a safe prophylactic strategy for high-risk LT recipients.